LEGAL POLICY FOR VISUM ET REPERTUM TEST IN EVIDENCE OF RAPE CRIME: PERSPECTIVE OF THE STATE COURT IN INDONESIA - Arief Budiono (Jurnal Hukum Replik, 2021)
Rape is a sexual crime and carries a maximum of 12 years in prison for the perpetrator under Indonesian law, but in practice it is rarely carried out and enforced. The judges' considerations contained in the decision of the case need to be questioned in relation to the protection of victims, as well as the tendency of judges to fulfill juridical, philosophical and sociological aspects in legal considerations as the basis for their sentences.Proof of the crime of rape is carried out by the forensic test method, namely visum et repertum. The result of the Visum et Repertum (VeR) is one of the valid evidences and is accepted by the District Court in Indonesia in handling cases of rape. VeR is carried out by doctors who have forensic expertise and the VeR test is a judge's consideration in deciding.Key words: Forensic, Test, Visum, Court, Rape